Examining the importance of the New Silk Roads for Africa and for global governance - (:unkn) unknown (My University, 2020)
In his chapter Thierry Pairault looks at Africa and the role it has in the new Silk Roads strategy. Various authors have seen the new Silk Roads strategy in Africa as a way to secure resources that China depends upon but is not self-sufficient in, or infra-structure for resources. The chapter raises the question of the place that the new Silk Roads could reserve for Africa and the 54 economies it comprises. It begins by focusing on Africa’s economic importance for China in investment and trade, contextualized with the engagement of other international actors, and then examines the strategic part that Africa as a whole and African states are likely to play. In arguing that Africa serves as a springboard for China in its definition of a new global governance, Thierry Pairault demonstrates that Africa’s importance in the new Silk Roads is currently more obvious from a geopolitical than from a strictly economic point of view.
Keywords: African Research